Repensando la autoficción desde la escena: una lectura de la paradoja de ser y no ser en la dramaturgia de Sergio Blanco - Luque, Gino (Pontificia Universidad Católica del Perú, 2023)
Despite the existence of performing practices that have explored the relationship between autobiography and fiction for a long time, theatrical autofiction has only recently begun to be studied. This is partly due to the particularities of theatrical communication that make traditional models of analysis, designed for narrative texts, unable to explain the dynamics of dramatic autofiction. This article proposes to rethink the theory of theatrical autofiction based on the inscription of the autofiction reading pacts in the conventions of theatrical reception. The discussion is based on the analysis of the dramaturgy of Sergio Blanco, whose work essentially explores the possibilities and limits of autofiction on stage.

Pese a existir prácticas escénicas que exploran las relaciones entre autobiografía y ficción desde hace mucho tiempo, la autoficción teatral ha empezado a ser estudiada solo recientemente. Ello responde, en parte, a particularidades de la comunicación teatral que hacen que los modelos de análisis tradicionales, pensados para textos narrativos, no logren explicar la dinámica de la autoficción dramática. Este artículo propone repensar la teoría sobre la autoficción teatral a partir de la inscripción de los pactos de lectura de la autoficción en las convenciones de recepción propias del teatro. La discusión se plantea a partir del análisis de la dramaturgia de Sergio Blanco, cuya obra indaga centralmente las posibilidades y límites de la autoficción en escena.
Rethinking Autofiction from the Stage: A Reading of the Paradox of To Be or Not To Be in the Dramaturgy of Sergio Blanco
Keywords: Theatrical autofiction; Autofictional pact; Theatrical reception; Sergio Blanco; Autoficción teatral; Pacto autoficcional; Recepción teatral; Sergio Blanco; https://purl.org/pe-repo/ocde/ford#6.02.06